IMPACT OF MELD SODIUM ON LIVER TRANSPLANTATION WAITING LIST - FREITAS,Alexandre Coutinho Teixeira de (2019)
ABSTRACT Background: Serum sodium was incorporated to MELD score for the allocation of liver transplantation In the USA in 2016. Hyponatremia significantly increased the efficacy of the score to predict mortality on the waiting list. Such modification was not adopted in Brazil. Aim: To carry out a simulation using MELD-Na as waiting list ordering criteria in the state of Paraná and to compare to the list ordered according to MELD score. Methods: The study used data of 122 patients waiting for hepatic transplantation and listed at Parana´s Transplantation Central. Two classificatory lists were set up, one with MELD, the current qualifying criteria, and another with MELD-Na. We analyzed the changes on classification comparing these two lists. Results: Among all patients, 95.1% of the participants changed position, 30.3% showed improvement, 64.8% presented worsening and 4.9% maintained their position. There were 19 patients with hyponatremia, of whom 94.7% presented a change of position, and in all of them there was an improvement of position. One hundred and one patients presented sodium within the normal range and 95% of them presented a change of position: Improved placement was observed in 18.8%, and worsened placement in 76.2%. Two patients presented hypernatremia and changed their position, both worsening the placement. There was a significant different behavior on waiting list according to sodium serum level when MELD-Na was applied. Conclusion: The inclusion of serum sodium caused a great impact in the classification, bringing benefit to patients with hyponatremia.